The Importance of Physical Medicine and Rehabilitation in Stroke: A Series of 189 Patients - Freitas Ferreira, Eduardo; Serviço de Medicina Física e Reabilitação, Hospital Professor Doutor Fernando Fonseca, Amadora, Portugal (2021)
Introduction: Stroke is one of the main causes of morbidity and mortality, representing the neurological pathology most frequently admitted to Internal Medicine (IM) departments. Rehabilitation is essential in optimizing the functionality of these patients.Material and Methods: Retrospective study of patients admitted to an IM department from January to December 2017 with a clinical diagnosis of stroke. The sample was characterized for sociodemographic and clinical variables. Functional variation during hospitalization was evaluated using the Barthel index. Statistical analysis was performed using the SPSS® software, version 23.0, considering a pvalue !0.05 as significant.Results: A total of 189 patients were included, which presented a median age of 78 years, a slightly female predominance (51.3%) and multiple comorbidities, such as hypertension (68.8%), dyslipidemia (47.6%) and diabetes mellitus (35.5%). The majority (77.8%) had imagiological translation, with 82.5% being of ischemic aetiology. The mortality rate was 10.1%. In 70.9% of cases, a Physical Medicine and Rehabilitation (PMR) assessment was requested. A statistically significant association was identified between the performance of rehabilitation and the in-hospital functionality variation (p=0.000).Conclusion: In this study, stroke occurred predominantly in a geriatric population, it was mostly due to ischemic aetiology and was associated with multiple comorbidities. The vast majority of patients were referred to PMR, with most of them presenting gain or maintenance of in-hospital functionality with rehabilitation performance. Thus, this study demonstrates the important role of PMR in minimizing functional deficits after stroke, allowing functionality improvement and facilitating socio-familiar integration.